Trends and molecular characteristics of carbapenemase-producing Enterobacteriaceae in Japanese hospital from 2006 to 2015. Issue 7 (July 2020) - Eda, Ryotaro; Nakamura, Masaki; Takayama, Yoko; Maehana, Shotaro; Nakano, Ryuichi; Yano, Hisakazu; Kitasato, Hidero
Abstract: Background: The increasing number of carbapenemase-producing Enterobacteriaceae (CPE) has become a global problem. Most carbapenemases detected in Japan are imipenemase, which is an imipenem-degrading enzyme with low ability; thus, CPE could have been overlooked. Therefore, this study aimed to detect and analyze CPE, without overlooking CPE showing the low minimum inhibitory concentration phenotype. Methods: CPE screening was conducted on 531 ceftazidime-resistant Enterobacteriaceae isolated from Kitasato University Hospital during 2006–2015. We confirmed the presence of the carbapenemase genes ( bla IMP, bla VIM, bla KPC, bla NDM, and bla OXA-48 ) by multiplex polymerase chain reaction. The detected CPE strains were analyzed by antimicrobial susceptibility testing, multilocus sequence typing, conjugal experiments, replicon typing, and plasmid profiling by restriction enzyme treatment. Results: The CPE detection rate in Kitasato University Hospital within the past 10 years was 0.0003% (nine CPE strains). These nine CPE strains were identified to harbor 8 bla IMP-1 or 1 bla NDM-5 . The CPE strains consisted of five species including Klebsiella pneumoniae and Citrobacter freundii . Six of eight bla IMP-1 were coded by IncHI2 plasmid, and the other two were coded by IncA/C plasmid. Plasmid profiling revealed that K. pneumoniae and C. freundii isolated from the same patient harbored the same plasmid. Conclusion: The CPE detection rate in this study was significantly lower than those previously reported in Japan. In one case, IncA/C plasmid transmission through different bacterial species within the body was speculated. Although the number of CPE detected was low, these results indicated that the resistance plasmid could spread to other bacterial species.